Relationship between inter-city air pollution levels and physical fitness parameters among sixth-grade Mongolian primary school boys, China, 2013-2016 - Cang Man; Takemasa Watanabe; Kana Oshimura; Nanding Baolige; Shuangjin Li (Elsevier, 2020)
Objectives: Adverse health effects due to air pollution have recently been recognized as a serious social problem in China. In this study, we investigated inter-city relationships between air pollution and physical fitness levels among Mongolian elementary school boys in five cities of the Inner Mongolia Autonomous Region (IMAR), China. Study design: Retrospective cross-sectional cohort study. Methods: Physical fitness measurements of 1443 male Mongolian sixth-grade children were obtained from an existing dataset from the year 2013-2016, and correlations were calculated between these measurements and the percentage of good air quality days for five different cities: Hohhot, Baotou, Chifeng, Bayannur, and Xilinhot. Results: Significant differences in the percentage of good air quality days from 2013 to 2016 were observed among the five cities studied. Statistical analysis showed a significantly positive correlation between good days and students' vital capacity, and a significantly negative correlation between good days and 50 ​m ​× ​8 shuttle run time for the students included in this study. Differences in the extent of air pollution among the study cities might account for differences in lung function and cardiovascular endurance levels in these Mongolian children. Conclusions: There is an urgent need for policy intervention to reduce air pollution levels in the IMAR. It is necessary to improve school physical education classes and physical training considering the current air pollution situation. Future research needs to replicate school year survey results from other cities, include longitudinal studies, and clarify the relationship between air pollution, physical exercise, and overall health.